Emerging Imaging Biomarkers in Crohn Disease. Issue 1 (February 2021) - Bane, Octavia; Gee, Michael S.; Menys, Alex; Dillman, Jonathan R.; Taouli, Bachir
Abstract : Abstract: In this review article, we present the latest developments in quantitative imaging biomarkers based on magnetic resonance imaging (MRI), applied to the diagnosis, assessment of response to therapy, and assessment of prognosis of Crohn disease. We also discuss the biomarkers' limitations and future prospects. We performed a literature search of clinical and translational research in Crohn disease using diffusion-weighted MRI (DWI-MRI), dynamic contrast-enhanced MRI (DCE-MRI), motility MRI, and magnetization transfer MRI, as well as emerging topics such as T1 mapping, radiomics, and artificial intelligence. These techniques are integrated in and combined with qualitative image assessment of magnetic resonance enterography (MRE) examinations. Quantitative MRI biomarkers add value to MRE qualitative assessment, achieving substantial diagnostic performance (area under receiver-operating curve = 0.8–0.95). The studies reviewed show that the combination of multiple MRI sequences in a multiparametric quantitative fashion provides rich information that may help for better diagnosis, assessment of severity, prognostication, and assessment of response to biological treatment. However, the addition of quantitative sequences to MRE examinations has potential drawbacks, including increased scan time and the need for further validation before being used in therapeutic drug trials as well as the clinic.